Changes in calcareous nannoplankton assemblages around the Eocene-Oligocene climate transition in the Hungarian Palaeogene Basin (Central Paratethys). (2nd September 2021) - Nyerges, Anita; Kocsis, Ádám T.; Pálfy, József
ABSTRACT: The Eocene-Oligocene climate transition (EOT) is the last major greenhouse-icehouse climate state shift in Earth history, ending the warm, ice-free early Palaeogene world and ushering in the Antarctic glaciation. This study is focused on the Hungarian Palaeogene Basin within the Central Paratethys, aiming to characterise the effect of the global cooling event in the calcareous nannoplankton assemblages and to reconstruct the palaeoenvironmental evolution of the region. Calcareous nannoplankton biostratigraphy is focused on documenting the NP21 Zone. Hierarchical cluster analysis allowed us to distinguish five successive assemblages. Thereby defined phases are compared with recently published trends in δ 18 O values and foraminiferal changes. Taxa with a preference for oligotrophic and warm surface waters dominate the lowest assemblage. The next assemblage contains taxa that indicate oligotrophic conditions but temperate surface water at the onset of the EOT. Nannoplankton abundance drops to a minimum in the third phase, when taxa adapted to cool surface waters gradually became dominant. A gradual rebound of nannoplankton abundance is observed in the fourth phase, possibly reflecting regional climate change related to the uplifting Alpine chain. After the end of the EOT, the youngest assemblage includes mostly eurytopic taxa which could tolerate an increased rate of freshwater and terrestrial influx.